BTN3A3 inhibits the proliferation, migration and invasion of ovarian cancer cells by regulating ERK1/2 phosphorylation - Chen, Sihan; Li, Zhangyun; Wang, Yanyan; Fan, Shaohua (Frontiers in Oncology, 2022)
Butyrophilin Subfamily 3 Member A3 (BTN3A3) is a type I transmembrane protein belonging to the immunoglobulin (Ig) superfamily, which is expressed in many cancers. Clinical data show that ovarian cancer patients with high expression of BTN3A3 have a longer survival time, but the mechanism of BTN3A3 in the occurrence and progression of ovarian cancer is still unclear. Here, we found that BTN3A3 knockdown can promote the proliferation, migration and invasion of ovarian cancer cells, while overexpression of BTN3A3 can inhibit the proliferation, migration and invasion of ovarian cancer cells. We analyzed the immunoprecipitated BTN3A3 complex by mass spectrometry and found that BTN3A3 binds to FGF2, and the overexpression of BTN3A3 leads to a decrease in the protein level of FGF2, which in turn leads to a decrease in the level of phosphorylation of ERK1/2. By increasing the protein level of FGF2, it was found that the level of ERK1/2 phosphorylation also increased. Finally, the cancer promotion phenomenon caused by BTN3A3 knockdown can be improved by using ERK1/2 inhibitor SCH772984. To sum up, BTN3A3 interacts with FGF2, which inhibits FGF2/ERK1/2 axis and ultimately inhibits the proliferation, migration and invasion of ovarian cancer cells. Our results suggest that BTN3A3 may be a prognostic marker and a potential therapeutic target for ovarian cancer.